1999
DOI: 10.1007/s004200050400
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive mechanism of gastric motility by whole-body vibration

Abstract: These results suggest that short-term exposure to WBV can suppress the gastric myoelectric activity, the responses on which may be mediating by neurohumoral effects as well as the mechanical effect of WBV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…This neuroendocrine response has been proposed to be the reason for reduced gastric motility during whole body vibration (Ishitake et al 1999), although direct mechanical influences could also play a role.…”
Section: Catecholaminesmentioning
confidence: 99%
“…This neuroendocrine response has been proposed to be the reason for reduced gastric motility during whole body vibration (Ishitake et al 1999), although direct mechanical influences could also play a role.…”
Section: Catecholaminesmentioning
confidence: 99%
“…and as to whole-body vibration impediment, many investigations about the effects of the spine on a driver are made in Europe and America [1][2][3][4] . On the other hand, there are quite a few studies on the effects of a circulatory organ system, a respiratory-organs system, and a digestive organ system [5][6][7][8][9] . Until now in our country, there is no full-scale investigation for the health disorders among workers who were occupationally exposed to whole-body vibration, there are a few investigations about some of forklift workers and taxi drivers [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…Di Loreto et al, 2004 andGoto andTakamatsu, 2005 have reported that the plasma concentration of epinephrine and norepinephrine are increased after WBV exercises. Ishitake et al, 1999 have suggested that short-term exposure to WBV can suppress the gastric myoelectric activity as a responses that would be mediated by neurohumoral effects due to the mechanical effect of WBV. It is possible to consider that this neuroendocrine response has been proposed to be the reason for reduced gastric motility during WBV exercise, although direct mechanical influences could also play a role.…”
Section: Hormonal Responses To Wbvmentioning
confidence: 99%